Recultured language in Indonesian English Language Teaching - Richard J. Stockton (Indonesian JELT, 2018)
While historically language and culture had been seen as separable, since Whorfianism they have commonly been viewed as intertwined. Today however, opposing political ideologies surprisingly work together to dissociate English language in ELT in Indonesia from its cultural background. They are the influence of globalist critical theory/political correctness which seeks not to oppressively impose Westernization, and the rise of nationalism, with its traditionalist education reemphasizing religion and the nation and disidentifying with Western values, fearing them a threat to local ones. The trend can be seen in the 2013 curriculum with its character-based curriculum, Indonesian teaching practice, and use of locally produced materials. Assessment using Purnell’s cultural competence model of widely used locally produced textbooks, Scaffolding (2008), Bright (2014), and Bahasa Inggris (2014), shows English in Indonesian ELT being stripped of liberal Anglo-American Western culture and values and recultured with Indonesian. The varieties of Englishes coming out of the process, Indonesian English and Islamic English, are not threatening to local language and culture as some have feared English is. Recultured English seems to put ELT at the service of nationalism, something English teaching may be caught off guard by. TESOL may prepare by becoming aware of traditionalist approaches to education.